2019
DOI: 10.1038/s42003-019-0675-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis identifies an escape route from the adverse lipogenic effects of liver X receptor ligands

Abstract: Liver X receptors (LXRs) are attractive drug targets for cardiovascular disease treatment due to their role in regulating cholesterol homeostasis and immunity. The anti-atherogenic properties of LXRs have prompted development of synthetic ligands, but these cause major adverse effects—such as increased lipogenesis—which are challenging to dissect from their beneficial activities. Here we show that LXR compounds displaying diverse functional responses in animal models induce distinct receptor conformations. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 67 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…The LXR transcriptional factor is critical in control of cholesterol homeostasis. When intracellular cholesterol content is increased, LXRs are activated to help drive cholesterol efflux by inducing the transcription of genes linked to the efflux of cholesterol, such as ATP binding cassette subfamily A member 1 (ABCA1) and ATP binding cassette subfamily G member 1 (ABCG1) 91 . LXR can also bind to SREBP to reduce its transcriptional activity, thus reducing de novo synthesis of cholesterol 92 …”
Section: Dysregulation Of Lipid Metabolism In Cancermentioning
confidence: 99%
“…The LXR transcriptional factor is critical in control of cholesterol homeostasis. When intracellular cholesterol content is increased, LXRs are activated to help drive cholesterol efflux by inducing the transcription of genes linked to the efflux of cholesterol, such as ATP binding cassette subfamily A member 1 (ABCA1) and ATP binding cassette subfamily G member 1 (ABCG1) 91 . LXR can also bind to SREBP to reduce its transcriptional activity, thus reducing de novo synthesis of cholesterol 92 …”
Section: Dysregulation Of Lipid Metabolism In Cancermentioning
confidence: 99%
“…On the other hand, this ligand-dependent interaction on LXRβ-LBD causes a selective dissociation of the transcriptional co-repressor NCOR1, which in turn affects target gene expression. Curiously, this phenomenon was not observed for LXRα (Belorusova et al, 2019). From these results, it is clear that important differences exist in the structural dynamics of LXRα, relative to those of LXRβ.…”
Section: The Tricks Behind the Structure Of Lxrsmentioning
confidence: 79%
“…Recently, using hydrogen/deuterium exchange mass spectrometry coupled to functional assays, Belorusova et al (2019) have revealed that LXRα-β LBD are differently stabilized depending on the ligand nature. They identified only in LXRα that the H3/H5 regions are preferentially stabilized by the different ligands (Belorusova et al, 2019).…”
Section: The Tricks Behind the Structure Of Lxrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Belorusova et al reported peptides of LXRα comprising the H3 and partial part of H5 correlated to high ABCA1 expression [30]. In addition, the differential relationship between target genes and LXRa isoforms in different patient groups also points to an oncogenic role for LXRa and a tumour suppressor role for LXRβ in TNBC tumours.…”
Section: Discussionmentioning
confidence: 99%